Caffeic Acid Phenethyl Ester as a Protective Agent against Nephrotoxicity and/or Oxidative Kidney Damage: A Detailed Systematic Review - Sumeyya Akyol; Veli Ugurcu; Aynur Altuntas; Rukiye Hasgul; Ozlem Cakmak; Omer Akyol (The Scientific World Journal)
Caffeic acid phenethyl ester (CAPE), an active component of propolis, has been attracting the attention of different medical and pharmaceutical disciplines in recent years because of its antioxidant, anti-inflammatory, antiproliferative, cytotoxic, antiviral, antifungal, and antineoplastic properties. One of the most studied organs for the effects of CAPE is the kidney, particularly in the capacity of this ester to decrease the nephrotoxicity induced by several drugs and the oxidative injury after ischemia/reperfusion (I/R). In this review, we summarized and critically evaluated the current knowledge regarding the protective effect of CAPE in nephrotoxicity induced by several special medicines such as cisplatin, doxorubicin, cyclosporine, gentamycin, methotrexate, and other causes leading to oxidative renal injury, namely, I/R models and senility.